Physical activity and general motor mode of the adult population in the system of ontogenesis - Zyurin E.A.,; Abramova T.F.,; Matveev A.P.,; Petruk E.N., (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the influence of physical activity during preparation for testing the GTO complex on the habitual motor mode of the adult population in various periods of age development. Methods and structure of the study. The experiment involved 480 men and 480 women aged from 25 to 70 years. To assess exercise tolerance, the Borg Rating of Perceived Exertion Scale (Borg CR10 Scale) was used. Heart rate and the number of steps taken per day were recorded using individual fitness gadgets. Results and conclusions. It was found that the most effective balance of load and recovery time is achieved with two classes per week. The implementation of the research results will help optimize preparation for performing tests of the GTO complex based on a balanced combination of household and physical activity, ensuring a high level of performance, improving physical qualities and motor skills, and the ability to fulfill the state requirements of the GTO complex for insignia while maintaining health.